Transcriptomic Study on Ovine Immune Responses to Fasciola hepatica Infection. - Yan Fu; Andreas L Chryssafidis; John A Browne; Jack O'Sullivan; Paul A McGettigan; Grace Mulcahy (Public Library of Science (PLoS), 2016)
BACKGROUND:Fasciola hepatica is not only responsible for major economic losses in livestock farming, but is also a major food-borne zoonotic agent, with 180 million people being at risk of infection worldwide. This parasite is sophisticated in manipulating the hosts' immune system to benefit its own survival. A better understanding of the mechanisms underpinning this immunomodulation is crucial for the development of control strategies such as vaccines. METHODOLOGY/PRINCIPAL FINDINGS:This in vivo study investigated the global gene expression changes of ovine peripheral blood mononuclear cells (PBMC) response to both acute & chronic infection of F. hepatica, and revealed 6490 and 2364 differential expressed genes (DEGS), respectively. Several transcriptional regulators were predicted to be significantly inhibited (e.g. IL12 and IL18) or activated (e.g. miR155-5p) in PBMC during infection. Ingenuity Pathway Analysis highlighted a series of immune-associated pathways involved in the response to infection, including 'Transforming Growth Factor Beta (TGFβ) signaling', 'Production of Nitric Oxide in Macrophages', 'Toll-like Receptor (TLRs) Signaling', 'Death Receptor Signaling' and 'IL17 Signaling'. We hypothesize that activation of pathways relevant to fibrosis in ovine chronic infection, may differ from those seen in cattle. Potential mechanisms behind immunomodulation in F. hepatica infection are a discussed. SIGNIFICANCE:In conclusion, the present study performed global transcriptomic analysis of ovine PBMC, the primary innate/adaptive immune cells, in response to infection with F. hepatica, using deep-sequencing (RNAseq). This dataset provides novel information pertinent to understanding of the pathological processes in fasciolosis, as well as a base from which to further refine development of vaccines.